Accountant’s Heroism to Report Fraud Collectively through Organizational Support - Syaiful Iqbal; Putri Wulanditya (Jurnal Ilmiah Akuntansi, 2023)
Financial fraud is possibly to be detected by accountants. However, not all accountants are willing to report fraud within the company. This study investigates the possibility of accountants’ heroic acts as whistleblowers individually or collectively in the presence or absence of organizational support. The data was collected from an experimental activity which was designed in the form of a 2x2 between-subject, by involving master accounting students and chartered accountant programs as participants. Then, data was analyzed using an independent sample t-test and analysis of variance to confirm the hypothesis. The results provide evidence that the likelihood of accountants intending to whistleblowing is more substantial when done collectively than individually, and the presence of organizational support strengthens whistleblowing intentions compared to those who do not receive organizational support. These findings contribute to supporting discussion in behavioral accounting and triggering companies to pay attention to the accountant's role as a whistleblower, and thus, support whistleblowing that accountants may carry out.